The Trend of Corporate Social Responsibility Spending by Public Sector Organisations: Evidence from Water Supply and Sanitation Authority in Tanzania - Mwandu, Rosemary; Kihanga, Ernest Pascal; Komba, Gabriel Vitus (Universitas Airlangga, 2024)
Background: Corporate Social Responsibility (CSR) has gained prominence as organisations increasingly recognise their role in contributing to social and environmental well-being. This study focuses on the CSR spending trends of Public Water Supply and Sanitation Authorities (WSSAs) in Tanzania, shedding light on their commitment to sustainable development through social and environmental initiatives. Objective: The study aim was to assess the trends of CSR spending by WSSAs in Tanzania over a five-year period (2015-2019). Specifically, the study aims to identify areas of CSR investment and assess the distribution of financial resources among various CSR activities undertaken by WSSAs. Method: Secondary data from 114 WSSAs were analysed using descriptive methods, specifically the line graphs to show CSR spending trends, and paired t-tests gauged significant changes over the five years. Results: The study finding reveals a gradual increase in CSR spending by WSSAs in Tanzania from 2015 to 2019. This upward trend indicates a sustained dedication to fulfil social and environmental responsibilities, contributing to the broader goal of sustainable development. The study also indicates a preference for directing CSR resources towards social-oriented activities. Notably, the highest spending was observed in local educational programmes and health services, while the lowest spending was observed on sports and cultural festivals. Conclusion: The study emphasises fostering policies to encourage ongoing CSR spending by WSSAs, especially in impactful education and health areas. Collaborative frameworks with local communities can address social and environmental challenges, aligning initiatives with community needs for holistic regional development. Keywords: Corporate social responsibility spending, Public sector organisations, Tanzania